The Library as a Service Point. The Case of the Bozen University Library: Planning, Building, Financing - Berger, Franz; Kempf, Klaus (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2000)
The temporary sites and the new buildings for the University in Bozen and in Brixen are provided and financed by the Autonomous Province of Bozen-Bolzano.